2017
DOI: 10.21037/acr.2017.09.02
|View full text |Cite
|
Sign up to set email alerts
|

Robotic approach in case of thymoma involving the left anonymous vein: a case report

Abstract: The robotic system has several technical advantages over the manual video thoracoscopic approach. It offers a high definition three-dimensional view and robotic arms are more comfortable to use, because they allow more precise, flexible, and intuitive movements. This case report describes a locally advanced thymoma in a 75-year-old male patient, excised through a robotic-assisted thymectomy with atypical resection of the infiltrated left upper lobe, the preservation of the left phrenic nerve and partial resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In fact, RATS is associated with lower mortality rate compared with open surgery and VATS, improved quality of life and reduced pain compared to open surgery, improved lymph node dissection and radicality regarding either anatomic segmentectomy [ 2 ] or a more extended resection for locally advanced non-small cell lung cancer [ 3 ] compared with VATS, with similar oncological outcomes. Furthermore, RATS provides enhanced outcomes when applied in complex cases and thymectomy in myasthenic patients [ 4 ]. Finally, it was demonstrated that both VATS and RATS are associated with similar costs when complications, length of stay and readmissions are taken into consideration.…”
Section: Group 81 Thoracic Surgerymentioning
confidence: 99%
“…In fact, RATS is associated with lower mortality rate compared with open surgery and VATS, improved quality of life and reduced pain compared to open surgery, improved lymph node dissection and radicality regarding either anatomic segmentectomy [ 2 ] or a more extended resection for locally advanced non-small cell lung cancer [ 3 ] compared with VATS, with similar oncological outcomes. Furthermore, RATS provides enhanced outcomes when applied in complex cases and thymectomy in myasthenic patients [ 4 ]. Finally, it was demonstrated that both VATS and RATS are associated with similar costs when complications, length of stay and readmissions are taken into consideration.…”
Section: Group 81 Thoracic Surgerymentioning
confidence: 99%
“…In these locally advanced cases, en bloc thymectomy by median sternotomy has been considered as the standard approach. However, the evolutionary development of robotic systems and the accumulation of robotic surgery experience have allowed some experienced robotic surgeons to approach more complex and difficult cases with these techniques (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%